The royals - Kelley, Kitty (New York : Warner Books, 1997)
A portrait of the men and women of the British royal family, drawing from documented sources and interviews with employees of the royal household, friends and relations, and members of Parliament, to discuss the private and public lives of Queen Elizabeth, Prince Charles, Princess Diana, the Duchess of York, and other royals.
Includes bibliographical references (pages 525-530) and index.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Keywords: Elizabeth -- II, -- Queen of Great Britain, -- 1926- -- Family; Queens -- Great Britain -- Biography; Windsor, House of